2017
DOI: 10.1016/j.neuropsychologia.2017.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms of mental fatigue elicited by sustained auditory processing

Abstract: Despite growing evidence that prolonged episodes of effortful listening can lead to mental fatigue, little work has been done to examine the patterns of brain activation associated with listening over time. In order to gain a better understanding of the nature of listening-related mental fatigue, this study characterized the effects of sustained auditory processing on brain activation in 19 adults with normal hearing. A 50-minute, auditory choice paradigm served as the fatiguing task. Mental fatigue was quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 93 publications
2
34
0
Order By: Relevance
“…Fatigue can manifest in performance decline (cognitive fatigue or muscle fatigue depending on the type of the task), in subjective reports, or in both (Ackerman and Kanfer 2009). The two measures do not necessarily correlate with each other (Ackerman and Kanfer 2009;Leavitt and DeLuca 2010;Gergelyfi et al 2015;Hornsby et al 2016;Takács et al 2019), but correlation between them has been found in some studies (Moore et al 2017;Hopstaken et al 2015b). The lack of close correlation between the two can be explained by a two-choice strategy: perception of difficulty can lead to increased effort to maintain performance or to goal aspiration reduction (Hockey 2011).…”
Section: Fatigue and Boredommentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigue can manifest in performance decline (cognitive fatigue or muscle fatigue depending on the type of the task), in subjective reports, or in both (Ackerman and Kanfer 2009). The two measures do not necessarily correlate with each other (Ackerman and Kanfer 2009;Leavitt and DeLuca 2010;Gergelyfi et al 2015;Hornsby et al 2016;Takács et al 2019), but correlation between them has been found in some studies (Moore et al 2017;Hopstaken et al 2015b). The lack of close correlation between the two can be explained by a two-choice strategy: perception of difficulty can lead to increased effort to maintain performance or to goal aspiration reduction (Hockey 2011).…”
Section: Fatigue and Boredommentioning
confidence: 99%
“…Boredom and fatigue are theoretically differentiated from each other by assuming that boredom is caused by underload, while fatigue is caused by overload (Pan et al 1994). However, fatigue can be accompanied by decreased arousal (Moore et al 2017) while boredom can be accompanied by increased arousal (Bailey et al 1976cited by Smith 1981. Noting the ambiguity in the literature, we take the perspective of Grandjean (1979 cited by Lal and Craig 2001) that boredom can be considered a special type of fatigue, and thus we will refer to the term "fatigue" within this paper as also including "boredom".…”
Section: Fatigue and Boredommentioning
confidence: 99%
“…With the development of science, people not only elucidate memory in various ways in theory, but also use various scientific and technological methods to conduct related research on memory (Fiene et al, 2018). At the behavioral level, many researchers use the he associative false memory under DRM paradigm, namely, word-based false memory (Moore et al, 2017); and some scholars use the event-based false memory under KK paradigm (Yang et al, 2017). In terms of science and technology, methods such as Event-Related Potential (ERP), functional Magnetic Resonance Imaging (fMRI), Eye Movement Technique (EMT), and Positron-Emission Tomography (PET) have emerged examine the neurophysiological mechanisms of memory (Li et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The fatigued state can be associated with decreased activity of the central nervous system, reflected in slowed information processing, decreased attention, and reduced arousal (Lim et al, 2010;Moore, Key, Thelen, & Hornsby, 2017;Murata, Uetake, & Takasawa, 2005). Thus, fatigued children may show reduced focus on the teacher's instructions and suffer from more frequent distractions caused by irrelevant events.…”
mentioning
confidence: 99%
“…The magnitude of the P300 response (difference between target and standard response) reflects the amount of processing capacity available for attention allocation to ongoing tasks (Polich, 2007). This processing capacity (and thus P300 amplitude) is modulated by arousal level (Kahneman, 1973;Polich, 2007), which is decreased in a fatigued state (Moore et al, 2017). Thus, a potential consequence of fatigue is diminished amplitudes of the P300 response (Key, Gustafson, Rentmeester, Hornsby, & Bess, 2017;Murata et al, 2005).…”
mentioning
confidence: 99%